Impact of current speed on mass flux to a model flexible seagrass blade. Issue 7 (10th July 2016) - Lei, Jiarui; Nepf, Heidi
Abstract: Seagrass and other freshwater macrophytes can acquire nutrients from surrounding water through their blades. This flux may depend on the current speed ( U ), which can influence both the posture of flexible blades (reconfiguration) and the thickness of the flux‐limiting diffusive layer. The impact of current speed ( U ) on mass flux to flexible blades of model seagrass was studied through a combination of laboratory flume experiments, numerical modeling and theory. Model seagrass blades were constructed from low‐density polyethylene (LDPE), and 1, 2‐dichlorobenzene was used as a tracer chemical. The tracer mass accumulation in the blades was measured at different unidirectional current speeds. A numerical model was used to estimate the transfer velocity ( K ) by fitting the measured mass uptake to a one‐dimensional diffusion model. The measured transfer velocity was compared to predictions based on laminar and turbulent boundary layers developing over a flat plate parallel to flow, for which K ∝ U 0.5 and ∝ U, respectively. The degree of blade reconfiguration depended on the dimensionless Cauchy number, Ca, which is a function of both the blade stiffness and flow velocity. For large Ca, the majority of the blade was parallel to the flow, and the measured transfer velocity agreed with laminar boundary layer theory, K ∝ U 0.5 . For small Ca, the model blades remained upright, and the flux to the blade was diminished relative to the flat‐plate model. A meadow‐scale analysis suggests that the mass exchange at the blade scale may control the uptake at the meadow scale. Key Points: Flow over sufficiently pronated, smooth blades resembles flow over a flat plate, on which a laminar boundary layer may develop For pronated blades, the laminar boundary layer model correctly predicted the measured transfer velocity, with K ∝ U 0.5 Mass exchange at the blade scale controls the uptake at the meadow scale